Investigating the role and mechanisms of bisphenol compounds in premature ovarian insufficiency using computational biology and bioinformatics - Deshui Kong; Yufei Nie; Haojie He; Hongyan Guo (Ecotoxicology and Environmental Safety, 2025)
Premature Ovarian Insufficiency refers to the premature decline in ovarian function before the age of 40, resulting in menstrual irregularities or complete cessation of menstruation, and affecting fertility. Widely used bisphenol compounds may have potential health effects, including premature ovarian insufficiency (POI). This study employs computational biology and bioinformatics to investigate the effects of bisphenols (BPs) on POI. Using bioinformatics tools, we identified potential target genes related to both bisphenols and POI, and conducted functional enrichment analysis. Further, we calculated differentially expressed genes for POI, extracted core networks, and explored immune function and screened core genes. Molecular docking and molecular dynamics simulations were used to explore the stable binding between bisphenols and core POI genes. Our results constructed a protein network of 56 potential target genes and extracted core subnetworks. Functional enrichment analysis indicated that estrogen metabolism, estrogen receptor pathways, steroid hormone metabolism, and carbohydrate and lipid metabolism may be involved in the process of BPs-induced POI. The differentially expressed genes obtained through further screening, CYP1A1 and CYP19A1, were subjected to molecular docking and dynamics simulations to reveal the mechanism by which bisphenols participate in estrogen metabolism through their stable binding. Our findings underscore the role of bisphenols in inducing POI and the potential mechanisms involved, providing new directions for further epidemiological and molecular biological research into this regulatory process.